ANALISIS DETERMINAN MASA TUNGGU PEKERJA TERDIDIK DI KOTA DENPASAR - Dewi, Kadek Dinda Mas Kencana; Marhaeni, A.A.I.N (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 10 (2023): Vol.12.No.10. OKTOBER 2023[650-724], 2023)
The aim of this research is; 1) to analyze the influence of age, skills, social networks, and parents' socioeconomic status simultaneously on the waiting period of educated workers in Denpasar City. 2) To analyze the effect of age, social network skills and parents' economic status partially on the waiting period of educated workers in Denpasar City. 3) To analyze the role of parents' socioeconomic status in moderating the influence of social networks on the waiting period of educated workers in Denpasar CityThe number of samples in this study were 100 samples. Data collection methods used are observation, structured interviews, and in-depth interviews. The data analysis technique used is moderation regression analysis. The results of this study indicate that age, skills, social networks and socio-economic status of parents simultaneously have a significant effect on the waiting period of educated workers in Denpasar City. Age, skills, social networks and parents' socio-economic status partially have a negative and significant effect on the waiting period of educated workers in Denpasar City. Parents' socioeconomic status moderates the influence of social networks in Denpasar City. Keywords: Educated unemployed, waiting period, age, skill, social network, socioeconomic status of parents.